👤

Développer les expressions suivantes : a)(7x -1)*+(5x-a)(2x-3). B) (4x-1)(4x+1)-(3x-2)*. C) (8x+2)*-5(2x+3)-(10x-1)*. *=au carré merci;)

Répondre :

Bonjour,

Développer les expressions suivantes :

a)(7x -1)²+(5x-a)(2x-3)

= 49x² - 14x + 1 + 10x² - 15x - 2a + 3a

= 49x² + 10x² - 14x - 15x - 2a + 3a + 1

= 59x² - 29x + a + 1

B) (4x-1)(4x+1)-(3x-2)²

= 16x² - 1 - (9x² - 12x + 4)

= 16x² - 1 - 9x² + 12x - 4

= 16x² - 9x² + 12x - 1 + 4

= 7x² + 12x + 3

C) (8x+2)²-5(2x+3)-(10x-1)²

= 64x² + 32x + 4 - 10x - 15 - (100x² - 20x + 1)

= 64x² + 32x + 4 - 10x - 15 - 100x² + 20x - 1

= 64x² - 100x² + 32x + 20x - 10x + 4 - 15 - 1

= - 36x² + 42x - 12